The Use of Acupuncture in the Treatment of a Downer Cow (Journal of Hama University, 2022)
The Study was conducted on /12/ mild to high yielding dairy cows /15- 25/ kg/ d in short time pretpartum divided into:1 . First Group: Included /6/ a Downer Cows with traditional and Acupuncture Treatmen.2. Second Group: Included /6/ a Downer Cows with traditional Treatmen only. The Clinical indications were within the physiological Range in all Groups.Biochemical analyzes were performed on blood serum to determine the concentrations of calcium, phosphorus, magnesium, and the activity of creatinekinase enzyme.differences between the. As for Ceratin kinas CK were found non-significant differences between the Research Groups. With respect to the concentration of calcium (p= 0.001 ) were significant differences between the Research groups. While there were no significant differences in phosphorus concentration between Research Groups. There was a significant difference in the concentration of magnesium when comparing the first and second Group. Observed when applying acupuncture treatment in the first group Combined with traditional treatment, recovery progression is faster and clear compared to the cows of the second group, to which the traditional treatment was applied, where improvement started from the seventh day.